Pengaruh Media Sosial Facebook Dan Testimoni Pelanggan Terhadap Kepercayaan Konsumen Pada Dealer Raja Jaya Motor Maumere - Akurama, Podensiana Oba; Rangga, Yoseph Darius Purnama; Tonce, Yosef (Universitas Nusa Nipa Maumere, 2026)
The rapid advancement of digital technology has compelled business owners to leverage social media as a core marketing and communication tool. Facebook remains a powerful platform to sustain customer relationships through targeted product information delivery and intensive online interactions. Concurrently, customer testimonials serve as critical social proof that directly alters consumer perceptions and enhances organizational trust. This study aims to empirically examine the influence of Facebook social media marketing and customer testimonials on customer trust at Dealer Raja Jaya Motor Maumere. Operating within a quantitative survey framework, data were gathered through structured questionnaires distributed to 100 verified customers and processed via multiple linear regression using SPSS. The findings demonstrate that both Facebook social media and customer testimonials exert a positive and statistically significant impact on customer trust, both partially and simultaneously.